2015
DOI: 10.1139/apnm-2014-0163
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine supplementation alleviates lipid metabolism derangements and protects against oxidative stress in non-obese hereditary hypertriglyceridemic rats

Abstract: The aim of this study was to estimate the effect of carnitine supplementation on lipid disorders and peripheral tissue insulin sensitivity in a non-obese animal model of insulin resistance, the hereditary hypertriglyceridemic (HHTg) rat. Male HHTg rats were fed a standard diet, and half of them received daily doses of carnitine (500 mg·kg(-1) body weight) for 8 weeks. Rats of the original Wistar strain were used for comparison. HHTg rats exhibited increased urinary excretion of free carnitine and reduced carni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…However, CPT-1 inhibition has been linked to reduced FAO, but upregulated glucose oxidation and improved whole-body glucose tolerance and insulin sensitivity in a mouse model [ 18 , 23 ]. Further supporting the potential clinical relevance of our findings, studies of carnitine supplementation have reported improved FAO, reduced oxidative stress, as well as improved lipid metabolism [ 24 26 ]. Overall, our study contributes to the growing body of evidence in support of pursing therapeutics centered on the CPT enzymes and/or their biochemical pathways.…”
Section: Discussionsupporting
confidence: 83%
“…However, CPT-1 inhibition has been linked to reduced FAO, but upregulated glucose oxidation and improved whole-body glucose tolerance and insulin sensitivity in a mouse model [ 18 , 23 ]. Further supporting the potential clinical relevance of our findings, studies of carnitine supplementation have reported improved FAO, reduced oxidative stress, as well as improved lipid metabolism [ 24 26 ]. Overall, our study contributes to the growing body of evidence in support of pursing therapeutics centered on the CPT enzymes and/or their biochemical pathways.…”
Section: Discussionsupporting
confidence: 83%
“…As carnitine acts as a transporter of long‐chain fatty acid from cytoplasmic compartment into mitochondria, where enzymatic beta‐oxidation and energy production occur, it may have participated in the reduction in any derangement of the testicular lipid metabolism that occurred in doxorubicin‐treated rats, contributing to the reduction of the damage in germ cells. Reinforcing this idea, in non‐obese hereditary hypertriglyceridemic rats carnitine improves the lipid metabolism and has potential protective action against oxidative stress produced in some metabolic syndrome‐related disorders (Cahova et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The pyruvate dehydrogenase activity was determined by measuring the 14 CO 2 produced by the decarboxylation of [1-14C]pyruvate in an assay containing 20-50 µg mitochondrial protein, as previously described (Cahova et al, 2015).…”
Section: Methodsmentioning
confidence: 99%